1934
DOI: 10.1017/s0022029900001035
|View full text |Cite
|
Sign up to set email alerts
|

Section D. The Diseases of Dairy Cattle

Abstract: As the tuberculin test forms the most important method of diagnosing tuberculous infection, the need for the adoption of a reliable and uniform technique in its application is obvious. The three methods most commonly employed are (1) the ophthalmic, (2) the subcutaneous, and (3) the intradermal test. Following the issue of a publication by Buxton and MacNalty(i) the so-called double intradermal test has become widely recognised as the most satisfactory method of diagnosis. Its reliability and superiority over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1936
1936
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Conversely, others have reported that earlysummer calving resulted in adequate forage availability due to the higher crude protein concentrations that met nutritional requirements for the female with minimal supplementation [76,77]. During times of drought, the potential for aflatoxins is increased due to the growth of some species of mold [78][79][80]. This poisonous by-product can lower reproductive efficiency through abnormal estrous cycles and abortions, a reduced growth rate, and decreased feed efficiency [80].…”
Section: Reproductive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, others have reported that earlysummer calving resulted in adequate forage availability due to the higher crude protein concentrations that met nutritional requirements for the female with minimal supplementation [76,77]. During times of drought, the potential for aflatoxins is increased due to the growth of some species of mold [78][79][80]. This poisonous by-product can lower reproductive efficiency through abnormal estrous cycles and abortions, a reduced growth rate, and decreased feed efficiency [80].…”
Section: Reproductive Performancementioning
confidence: 99%
“…During times of drought, the potential for aflatoxins is increased due to the growth of some species of mold [78][79][80]. This poisonous by-product can lower reproductive efficiency through abnormal estrous cycles and abortions, a reduced growth rate, and decreased feed efficiency [80]. The quality of the forage determines cattle forage intake, forage protein content, and mineral content, so when only low-quality forage is available, supplementation is often required [61,[81][82][83].…”
Section: Reproductive Performancementioning
confidence: 99%